Development of the GABAergic and glutamatergic neurons of the lateral hypothalamus - Zhou, Xunlei; Risold, Pierre-Yves; Alvarez-Bolado, Gonzalo (Journal of chemical neuroanatomy, 2021)
In the last few years we assist to an unexpected deluge of genomic data on hypothalamic development and structure. Perhaps most surprisingly, the Lateral Zone has received much attention too. The new information focuses first of all on transcriptional heterogeneity. Many already known and a number of hitherto unknown lateral hypothalamic neurons have been described to an enormous degree of detail. Maybe the most surprising novel discoveries are two: First, some restricted regions of the embryonic forebrain neuroepithelium generate specific LHA neurons, either GABAergic or glutamatergic. Second, evidence is mounting that supports the existence of numerous kinds of “bilingual” lateral hypothalamic neurons, expressing (and releasing) glutamate and GABA both as well as assorted neuropeptides. This is not accepted by all, and it could be that genomic researchers need a common set of rules to interpret their data (sensitivity, significance, age of analysis). In any case, some of the new results appear to confirm hypotheses about the ability of the hypothalamus and in particular its Lateral Zone to achieve physiological flexibility on a fixed connectivity (“biochemical switching”). Furthermore, the results succinctly reviewed here are the basis for future advances, since the transcriptional databases generated can now be mined e.g. for adhesion genes, to figure out the causes of the peculiar histology of the Lateral Zone; or for ion channel genes, to clarify present and future electrophysiological data. And with the specific expression data about small subpopulations of neurons, their connections can now be specifically labeled, revealing novel relations with functional significance.
Gesehen am 18.10.2021